Back Cover: Synthesis of Soluble, Alkyne‐Substituted Trideca‐ and Hexadeca‐Starphenes (Chem. Eur. J. 40/2014). Issue 40 (26th September 2014) - Rüdiger, Elias C.; Porz, Michael; Schaffroth, Manuel; Rominger, Frank; Bunz, Uwe H. F.
<x xml:space="preserve">Abstract</x> Starphenes were obtained by the Ni‐catalyzed trimerization (Yamamoto reaction) of suitable ortho‐dibromotetracene and ortho‐dibromopentacenes. The starphenes are highly soluble due to the attached triisopropylsilyl (TIPS)‐ethynyl groups. These bulky groups also distort the molecular structure of the starphenes. The red starphene in the foreground is tetracene based, whereas the orange star is dibromopentacene based, representing three hexacenes, sharing one central ring. The starphenes are surprisingly stable and showed weak absorption bands in the visible spectra. For more information, see the Communication by U. H. F. Bunz et al. on page ff. 12725.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>